2021
DOI: 10.21203/rs.3.rs-206230/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of antibiotic prescriptions: a knowledge, attitude and practice survey among physicians in tertiary hospitals in Nigeria

Abstract: BackgroundAs part of the Global Action Plan against antimicrobial resistance (AMR), countries are required to generate local evidence to inform context-specific implementation of national action plans against AMR (NAPAR). We aimed to evaluate the knowledge, attitude, and practice (KAP) regarding antibiotic prescriptions (APR) and AMR among physicians in tertiary hospitals in Nigeria, and to determine predictors of KAP of APR and AMR. MethodsIn this cross-sectional study, we enrolled physicians practicing in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…The least frequent reason being to maintain the relationship with the patient. Both indulgence and fear have been the most frequent attitudes found to influence the improper prescription of antibiotics in previous studies both in Colombia and other countries of the world [ 6 , 11 , 12 , 13 ]. It is important to note that most prescribers in the present study were general practitioners with little professional experience, which could explain this type of attitudes that influence these behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The least frequent reason being to maintain the relationship with the patient. Both indulgence and fear have been the most frequent attitudes found to influence the improper prescription of antibiotics in previous studies both in Colombia and other countries of the world [ 6 , 11 , 12 , 13 ]. It is important to note that most prescribers in the present study were general practitioners with little professional experience, which could explain this type of attitudes that influence these behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical prescribing, making antibiotic choices based on experience and not on AST, is the predominant mode of prescribing in this setting, similar to findings previously reported (30). While efforts to change this practice towards more evidence-based prescribing are established or expanding in many countries in the northern hemisphere (31,32), uptake in the southern hemisphere is low. In Nigeria, one study found that none out of 12 surveyed tertiary hospitals had a formal AMS structure (33).…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review and meta-analysis included 39 (Thriemer et al, 2013;Abera et al, 2014;Pereko et al, 2015;Simba et al, 2016;Asante et al, 2017;Farley, 2017;Genga et al, 2017;Tafa et al, 2017;El Sherbiny et al, 2018;Seid and Hussein, 2018;Mate et al, 2019;Sunusi et al, 2019;Fetensa et al, 2020;Gemeda et al, 2020;Kabba et al, 2020;Mengesha et al, 2020;Nisabwe et al, 2020;Sindato et al, 2020;Wesangula et al, 2020;Zulu et al, 2020;Aworh et al, 2021;Babatola et al, 2021;Chukwu et al, 2021;Gebeyehu et al, 2021;Geta and Kibret, 2021;Mostafa et al, 2021;Ogoina et al, 2021;Russom et al, 2021;Adegbite et al, 2022;Belachew et al, 2022;Dejene et al, 2022;Kanyike et al, 2022;Mudenda et al, 2022;Paye and McClain, 2022;Tembo et al, 2022;Abubakar and Sárváry, 2023;Davwar et al, 2023;Maarouf et al, 2023;Otieku et al, 2023) published studies involving 18,769 study subjects. The review included primary studies with a remarkably varied sample size, ranging from just 47 (Adegbite et al, 2022) to 2,477…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the included studies, 33 were cross-sectional (Thriemer et al, 2013;Abera et al, 2014;Pereko et al, 2015;Simba et al, 2016;Asante et al, 2017;Farley, 2017;Genga et al, 2017;Tafa et al, 2017;El Sherbiny et al, 2018;Seid and Hussein, 2018;Mate et al, 2019;Fetensa et al, 2020;Gemeda et al, 2020;Mengesha et al, 2020;Nisabwe et al, 2020;Sindato et al, 2020;Zulu et al, 2020;Aworh et al, 2021;Babatola et al, 2021;Chukwu et al, 2021;Gebeyehu et al, 2021;Geta and Kibret, 2021;Mostafa et al, 2021; FIGURE 1 PRISMA flow diagram explaining selection of primary studies in Africa. 10.3389/fmicb.2024.1345145 Frontiers in Microbiology 05 frontiersin.org Ogoina et al, 2021;Russom et al, 2021;Adegbite et al, 2022;Dejene et al, 2022;Kanyike et al, 2022;Mudenda et al, 2022;Paye and McClain, 2022;Abubakar and Sárváry, 2023;Davwar et al, 2023;Maarouf et al, 2023), while six studies followed a cohort study design (Sunusi et al, 2019;Kabba et al, 2020;Wesangula et al, 2020;Belachew et al, 2022;Tembo et al, 2022;O...…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation